Proteome-wide Mendelian randomization and therapeutic targets for bladder cancer - Meng-Hua Wu; Min-Heng Zhang; Xiao-Dong Hu; Hai-Xia Fan (BMC Urology)
Abstract Objective To identify therapeutic protein targets for bladder cancer (BCa) using Mendelian randomization (MR) and assess potential adverse effects of these targets. Methods A proteome-wide MR study was conducted to determine causal relationships between plasma proteins and BCa risk. In the discovery stage, the plasma proteins (Exposure) were sourced from the R10 of Finnish database, Olink (619 samples across 2925 proteins) and SomaScan (828 samples across 7596 proteins), and Iceland database. In the replication stage, plasma proteins (Exposure) were sourced from the UK-Biobank-PPP database (54,219 participants and 2940 proteins). Summary-level data for BCa (Outcome) were obtained from the UK Biobank (UKB-SAIGE: cancer of bladder) in the discovery phase and the FinnGen consortium (FinnGen R11: cancer of bladder) in the replication phase. Colocalization and fix-effect meta-analyses were performed to validate MR findings. Finally, phenome-wide association study (Phe-WAS) was conducted to explore the side effects of druggable proteins utilizing UKB-SAIGE encompassing 783 phenotypes. Results The MR analysis identified PSCA, LY6D, and SLURP1 as proteins with a genetic association to BCa risk. SLURP1 was confirmed in the replication phase, with a meta-analysis showing an odds ratio of 1.50 (95% CI: 1.30–1.74, P < 0.001). Phe-WAS indicated potential side effects for these targets. Conclusion This study provides insights into the causal relationships of plasma proteins with BCa, identifying PSCA, LY6D, and SLURP1 as potential therapeutic targets, with implications for future BCa treatment strategies.